2021
DOI: 10.1177/00169862211025452
|View full text |Cite
|
Sign up to set email alerts
|

Are Gifted Students Adapting Their Self-Regulated Learning Processes When Experiencing Challenging Tasks?

Abstract: Self-regulated learning (SRL) promotes both current and future academic achievement and must be adapted based on task demands. To develop SRL, gifted students must have opportunities to experience optimally challenging tasks. Gifted students’ past experiences (or lack thereof) with challenging tasks affects how they approach current tasks, which affects how they will approach challenges in the future. The current study used a two-stage approach to examine the extent to which Honors College students are able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…Hence, a need for cognition is expressed in the need for higher level content, and a mastery goal orientation is apparent in the preference for growth over simplicity. These findings mirror some of the findings from Ridgley et al (2022), who found that students hold positive student perceptions of academic challenges in gifted programs. Our findings are indicative of a positive attitude of how these cognitive "needs" are met within gifted programming, and this is especially important since the perception of a challenge influences how such challenges are approached.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Hence, a need for cognition is expressed in the need for higher level content, and a mastery goal orientation is apparent in the preference for growth over simplicity. These findings mirror some of the findings from Ridgley et al (2022), who found that students hold positive student perceptions of academic challenges in gifted programs. Our findings are indicative of a positive attitude of how these cognitive "needs" are met within gifted programming, and this is especially important since the perception of a challenge influences how such challenges are approached.…”
Section: Discussionsupporting
confidence: 86%
“…It is of interest to understand if gifted students have positive perceptions of cognitive challenges, since how one perceives a challenge will influence how the challenge will be approached (Ridgley et al, 2022). The pursuit of these challenges relates to motivational factors including the need for cognition.…”
Section: Need For Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, differences were found between GHA and TA regarding the variables of self-efficacy, control of learning beliefs, and assignment value, especially within a low-SES environment. Researchers have found that gifted students generally have higher academic self-efficacy than their typical achieving peers (Malpass et al, 1999; Ridgley et al, 2022; Siegle et al, 2010). Gifted students are more likely to report a higher sense of control and to attribute success and failure to internal factors (Assouline et al, 2006; Rinn et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Gifted achievers are more likely to attribute success to their ability and effort, while failure is attributed to a lack of effort (Assouline et al, 2006; Rinn et al, 2014). Studies have shown that gifted students should receive adequate challenges so as not to be easily bored, as boredom can also affect their motivation (Lens & Rand, 2000; Ngiamsunthorn, 2020; Phillips & Lindsay, 2006; Ridgley et al, 2022; Snyder et al, 2019). Studies have recommended adjusting the task level for gifted students to draw and sustain their attention and to challenge them because overly easy tasks tend to bore them.…”
Section: Literature Reviewmentioning
confidence: 99%